Emotional intelligence development: the implementation of transformative learning through digital technologies in tourism - a study protocol. (21st February 2023) - Kallou, Sofia; Kikilia, Aikaterini; Kalogiannakis, Michail; Zacharis, Nick Z.
In today's era of globalisation and intense competition between tourism businesses, employees distinguished for their emotional abilities, good interpersonal relationships and teamwork, contribute to the quality and efficiency of the provided services. In this regard, the need for new training and educational programs in Emotional Intelligence in the tourism sector is more than ever relevant, as tourism businesses demand graduates that can be more efficient and capable of servicing and satisfying customers. Moreover, the new challenges that arise in education and training lead to the adaption of digital learning environments, and new teaching methods. Furthermore, Transformative Learning, as an adult learning theory, leads individuals, through critical reflection and constructive dialogue, to evaluate their past values and beliefs and shift their worldview implementing new perspectives and attitudes which are more functional. The purpose of this protocol study is to investigate the learning effectiveness of Transformation Learning as a pedagogical tool for the development of Emotional Intelligence for tourism employees, through digital learning technologies.